Understanding Social Media Influencer Attributes: Developing and Validating a Measurement Model - Mohamed, Nurashikin Nazer; Jaafar, Norizan (New Advances in Business, Management and Economics Vol. 4, 2025)
Consumers tend to pay attention to the information shared by influencers due to the influencers’ first-hand knowledge of products or services. The use of social media influencers in marketing is a relatively new tactic that is becoming a common marketing trend in Malaysia. In Malaysia, consumers prefer to seek information from social media influencers since they rely more on the recommendations made by those influencers. Since influencers have become such influential figures in shaping consumer behaviour and influencing purchasing decisions, marketers need to understand the characteristics of social media influencers. The purpose of this study is to develop and validate the instruments for measuring the social media influencer attribute construct. Each of the respondents for this study must be a female between the ages of 18 and 56 and must have viewed a video on YouTube in which a beauty influencer gave her opinion on a cosmetic product. Hence, this study was divided into two parts. First, for the pilot study, this study used convenience and purposive sampling methods to select 100 respondents for exploratory factor analysis (EFA) using SPSS. Next, this study used purposive and snowball sampling for the actual study to select 393 respondents for confirmatory factor analysis (CFA) via IBM- SPSS-AMOS version 24. In structural equation modelling (SEM), a number of fitness indices were used to assess how well a model fits the data that are being investigated. The findings showed that the social media influencer attribute construct measurement model fulfilled the requirements for construct validity and reliability, suggesting that it can be used in future research. This study successfully established and validated the essential instruments for measuring the social media influencer attributes construct for practical use.